Emission Factors and Inventories of Carbonaceous Aerosols from Residential Biomass Burning in Guizhou Province, China - Wang, Yan-Ni; Cheng, Yan; Gu, Zhao-Lin; Yang, Jing-Ting; Ren, Huan-Huan (Atmosphere, 2022)
Biomass combustion results in the emission of substantial amounts of carbonaceous aerosols. Here, we report the emission characteristics of organic carbon (OC) and elemental carbon (EC) from biofuel combustion according to field measurements in rural households in Guizhou Province, China. The average emission factor of OC was 0.57 ± 0.16 g kg−1 for firewood burning, which was lower than that for crop straw burning. The average emission factor of EC was 1.1 ± 0.63 g kg−1 for firewood burning, which was higher than most crop straw burning, including corn (0.68 ± 0.29 g kg−1), rice (0.48 ± 0.40 g kg−1), and soybean (0.17 ± 0.21 g kg−1). The average OC/EC ratios from crop straw burning were high, 14.2 for rice straw burning, 11.7 for soybean straw burning, 5.1 for corn straw burning, and 2.8 for pepper straw burning. The average OC/EC ratio of firewood was the lowest at 0.54. In 2019, the estimated emissions of OC and EC from residential biomass fuel combustion in Guizhou Province were 3.6 and 5.6 Gg, respectively. Firewood burning was the primary contributor to total residential biofuel OC (≈81%) and EC (≈97%) emissions. High-emission areas included Tongren, Qiandongnan, and Qiannan.